Cooperation in the law of transboundary water resources - Leb, Christina (Cambridge : Cambridge University Press, 2013)
'Climate change, population growth and the increasing demand for water are all capable of leading to disputes over transboundary water systems. Dealing with these challenges will require the enhancing of adaptive capacity, the improving of the quality of water-resources management and a reduction in the risk of conflict between riparian states. Such changes can only be brought about through significant international cooperation. Christina Leb's analysis of the duty to cooperate and the related rights and obligations highlights the interlinkages between this duty and the principles of equitable and reasonable utilisation and the prevention of transboundary harm. In doing so, she considers the law applicable to both international watercourses and transboundary aquifers, and explores the complementarities and interaction between the rules of international water law and the related obligations of climate change and human rights law'--
Introduction -- Cooperation between sovereign states -- Development of international water law -- The duty to cooperate and concurrence of principles -- Informing cooperation -- Adoption of joint measures -- International protection of vital human water needs -- Emerging international cooperation on global water challenges -- Conclusion -- Annex. Consideration of cooperation in international treaties.
Includes bibliographical references (pages 299-320) and index.
Keywords: Water rights (International law); Water resources development -- Law and legislation; Watershed management -- Law and legislation; Riparian rights; Watershed management -- International cooperation; Water resources development -- International cooperation; Water-supply -- Management